Seismic Expression of North Sulawesi Subduction Zone - Herman Darman (Ikatan Ahli Geologi Indonesia, 2011)
Sulawesi Sea and its surrounding area is an active tectonic region. Many studies were done to understand the tectonics in this area. For this reason, several seismic vintages were acquired in the Sulawesi Sea (Celebes Sea) area. The seismic lines were published in:1977 by Hinz: single multichannel reflection seismic (MRS) profile1979 by Hamilton: single trace reflection seismic lines1987 by Hinz and 1989 by Fechner: seismic data acquired by SONNE-cruise 49 in Mindanao area, at the eastern end of the Celebes Sea Basin.1994 by Zen and Hinz: seismic data acquired by SONNEcruise 94, sponsored by German institutions.1997, by Beiersdorf et al.: seismic data acquired by SONNE-cruise 98 which also did geological and geochemical investigations.This article shows the seismic expressions in the southern margin of the Sulawesi Sea, which is the subduction zone in the north of Sulawesi North arm and known as North Sulawesi Trench.